A Collaborative Learning Model for Developing Problem-Solving Skills in Mathematics: the Role of Respect and Support - Isaiah Dookurong Dilor (Universitas Negeri Surabaya, 2025)
This study examined the influence of a respectful and supportive collaborative learning environment on Senior High School Year 3 (SHS3) students’ problem-solving skills and mathematics achievement in Ghana. A mixed-methods approach was adopted with open-ended questionnaire and achievement test, employing Braun and Clarke’s thematic analysis for qualitative data and paired-sample t-test statistics for quantitative analysis. The intervention focused on promoting mutual respect, peer support, and structured collaboration during mathematics problem-solving tasks. Pre-test findings highlighted barriers such as fear of negative peer judgment, low confidence, avoidance of challenging problems, limited knowledge of problem-solving strategies, and surface-level learning. Post-test results revealed marked improvements, including enhanced confidence, constructive peer interaction, persistence, deeper learning, accuracy, and the use of diverse strategies. Statistical results from the SHS 3 further confirmed significant gains in mathematics achievement after the intervention. These findings demonstrate that fostering respect and support within collaborative learning environments can strengthen both problem-solving competencies and academic performance. The study recommends that mathematics educators adopt respect-based collaborative approaches to cultivate positive peer dynamics, encourage active engagement, and develop higher-order thinking skills among students.